1972
DOI: 10.1037/h0032623
|View full text |Cite
|
Sign up to set email alerts
|

Methodological issues and racial (black-white) comparisons on the MMPI.

Abstract: Racial (black-white) comparisons were made on four dependent measures (MMPI) to probe three issues generated by previous inconsistent findings in this area. Issues were (a) defining primary sources of variance, (6) comparability of dependent measures, and (c) effect of selection criteria, in the form of common requirements for profile validity, on outcome. White counterparts were matched with 160 blacks on sex, socioeconomic status (education and occupation), hospital status, age, and duration of illness. Phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0

Year Published

1973
1973
1990
1990

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…These findings were similar to some of the differences that have been reported in the way that the Black population scores on the MMPI. For example, there are indications that Black psychiatric patients tend to score higher on the Psychopathic Deviate scale (Davis et al, 1973), the Schizophrenia scale (Butcher et al, 1983;Costello et al, 1973;Costello et al, 1972;Davis et al, 1973;Genther &Graham, 1976;Miller et al, 1968;Miller et al, 1961), and the Hypomania scale (Butcher et al, 1983;Costello et al, 1972;Genther &Graham, 1976;Holcomb & Adams, 1982;Miller er al., 1968;Miller et al, 1961), whereas Blacks may be inclined to obtain a lower score on the Masculinity-Femininity scale (McCreary & Padilla, 1977). Ir would appear that these MMPI scales measure similar characteristics to those mentioned in the previous paragraph as characterizing rhe differences found with the MCMI.…”
Section: )mentioning
confidence: 96%
“…These findings were similar to some of the differences that have been reported in the way that the Black population scores on the MMPI. For example, there are indications that Black psychiatric patients tend to score higher on the Psychopathic Deviate scale (Davis et al, 1973), the Schizophrenia scale (Butcher et al, 1983;Costello et al, 1973;Costello et al, 1972;Davis et al, 1973;Genther &Graham, 1976;Miller et al, 1968;Miller et al, 1961), and the Hypomania scale (Butcher et al, 1983;Costello et al, 1972;Genther &Graham, 1976;Holcomb & Adams, 1982;Miller er al., 1968;Miller et al, 1961), whereas Blacks may be inclined to obtain a lower score on the Masculinity-Femininity scale (McCreary & Padilla, 1977). Ir would appear that these MMPI scales measure similar characteristics to those mentioned in the previous paragraph as characterizing rhe differences found with the MCMI.…”
Section: )mentioning
confidence: 96%
“…In addition, the differences from unmatched comparisons should be attenuated on the matched comparisons. Furthermore, in light of the methodological criticisms of Costello, Tiffany, and Gier (1972)) the effects of applying validity rules and the different inferences obtained by comparing individual scales as well as clusters of scale scores are examined. The comparison of all profiles vs. only valid profiles clarifies whether obtained differences simply reflect response set factors, such as the ability of the person to read and understand the items.…”
mentioning
confidence: 99%
“…Costello et al (1972) made several important methodological refinements, but seemed to err by analyzing differences between racial groups on males and females together.…”
mentioning
confidence: 99%
“…Recent reviews of the literature (Costello, Tiffany, & Gier, 1972;Gynther, 1972), cited a number of studies that investigated racial (black/white) differences on MMPI performance. These results were inconclusive relative to personality characteristics, as some researchers reported no significant differences and others showed higher clinical scale scores for blacks than whites.…”
mentioning
confidence: 99%
“…With differences found within and between studies, the data interpretations have been as varied as the results. Costello et al (1972) have concluded that "methodological sophistication, populations and sample sizes have varied broadly. As a result, the findings have been inconsistent and, a t times, even contradictory [p. "normal" samples of blacks and whites on M M P I subtests have been few, the present study dealt with this population.…”
mentioning
confidence: 99%